Climate Change Threat in Jaipur: Mitigating and Sustainable Attributes Through Carbon Footprint Reduction - Anindita Bhattacharjee; Tania Das; Mansi Singh; Swati Bhargava; Gitika Joshi; Prachi Golhar; Akshey Bhargava (International Journal of Climate Conditions, 2026)
Challenges of climate change are significantly increasing on a forward time scale. Such a phenomenon is predominantly seen in urban sectors where population is rapidly increasing, thereby resulting in extensive resource consumption leading to release of significant carbon footprint. An attempt has been made in the present paper by the authors initially to assess the carbon footprint of Jaipur, Rajasthan on a backward and forward time scale partly to suggest mitigating measures and partly to link it with carbon credit schemes for achieving circular economy and providing sustainability. Research on assessment of carbon footprint has been done primarily on population, resource consumption in the form of LPG, power, and automobile, sewage, solid waste, housing, industry, other miscellany sources and secondly predicting on futuristic time scales of 1931, 1941 and 1951. Carbon footprint of automobile sector is done individually in respect of 2-wheelers, 4-wheelers, buses, goods vehicles, and other vehicles and predicted estimations done for the years 1931, 1941 and 1951. The mitigating measures particularly in the form of green infrastructure or urban forestry are evaluated to achieve towards d neutrality and link with carbon credit schemes to achieve circular economy and infuse sustainability. Although tropical rainforests are considered as one of the most important ecosystems used for the mitigation of the climate change, but it is quite far and away. The authors also attempted to assess the extent of green infrastructure required to achieve 30,50,70,90, and 100 percent carbon footprint reduction.
Keywords: Carbon footprint reduction; Carbon neutrality; Urban resilience; adaptation strategies; green buildings and urban sustainability; greenhouse gas emissions; urban forestry; urban heat island effect